Nursing practices in the prevention of cervical cancer - Santos, Luis Henrique Costa; Carvalho, Ramon Santos; Paz, Antonio Bezerra da (JRG Journal of Academic Studies, 2023)
Cervical cancer is one of the most common neoplasms among women, being one of the causes of death from cancer, despite being one of the few preventable neoplasms. The Cancer Institute highlights the disease as the first of the most incident in some regions. The objective of this study was to describe the role of nurses in the early detection of cervical cancer in asymptomatic women, by means of cytopathological examination; Achieve the HPV vaccination target in at least 80% of the target population, to reduce the incidence of cancer in the coming decades; Educate adolescents and young people on the importance of HPV immunization in order to reduce cases; Perform the Pap smear in conjunction with vaccination, completing the actions to prevent this cancer; Raise awareness of the importance of prevention and early diagnosis of cervical cancer. The research carried out was of the descriptive and documented bibliographic review type, where journal articles and materials available on the Internet were used. It was observed the importance of nurses to have knowledge about the subject, so that they can guide and care for users of the public health system, in an attempt to reduce cases of cervical cancer.